PERLINDUNGAN HUKUM TERHADAP DEBITUR PADA PERJANJIAN PEMBIAYAAN KONSUMEN DENGAN PEMBEBANAN JAMINAN FIDUSIA - Subadra Yani (UNES Law Review, 2020)
Consumer financing is financing activities for the procurement of goods based on consumer needs with installment payments regulated in Article 1 number 7 of Presidential Regulation No. 9 of 2009 concerning Financing Institutions. To reduce losses if debtors default, the financing of motor vehicle consumers is charged with fiduciary guarantees regulated in Law Number 42 of 1999 concerning Fiduciary guarantees. In practice, the implementation of consumer financing for motor vehicles often results in problems that harm the debtor (consumer) especially when the acquisition of fiduciary collateral items if the debtor (consumer). therefore it is necessary to conduct research on how the legal protection of debtors in consumer financing agreements with the imposition of fiduciary guarantees. The data used are secondary supporting data collected through library studies and primary data as supporting data conducted through field studies using interview techniques. The results of the study found that: legal protection for debtors in consumer financing agreements with the imposition of fiduciary guarantees has been regulated in several relevant laws and regulations, namely the Consumer Protection Act, the Fiduciary Guarantee Act, the Financial Services Authority Act and the implementing regulations. If a consumer is harmed by a finance company, the debtor (consumer) can sue the finance company because of an unlawful act and may even ask for a criminal act.